Communication Strategies Used by the English Learners of Saturday Discussion at the Centre for Language and Culture (CLC) - Lilik Sri Wahyuningsih (Universitas Pendidikan Mandalika, 2018)
There are some factors influence someone in expressing the language, such as experiences, knowledge, age and cultural background. Yet, since the communication must go on with any limitedness, the learners should employ some strategies in order to keep holding communication. The strategies used in communication are identified as communication strategies. This present study analyses on an investigations into communication strategies used by the learners of Saturday discussion at the Centre for Language and Culture (CLC) Surabaya. The learners are the participants of Saturday Discussion at CLC Surabaya. In this study, the researcher wanted to find out kinds of communication strategies used by the learners, differences and similarities between young and adult learners in applying communication strategies, and how they apply communication strategies in their discussions. In her study, she applied communication strategies typology proposed by Tarone and Faerch and Kasper which consist of transfer from native language, overgeneralization, prefabricated pattern, overelaboration, epenthesis or vowel insertion, avoidance which can be subdivided into topic avoidance, semantic avoidance, appeal to authority, message abondanment and language swicth. Appeal to authority can be subdivided into paraphrase, word coinage, and circumlocution. Tarone, divided the communication strateies as formal reduction strategies, functional reduction strategies, and achievement strategies. To answer the research questions, she used descriptive qualitative approach. In collecting the data she carried out observation, and interview. In her study she found out that there were ten communication strategies used by the learners, they are message abondanment, appeal to authoriy, and language switch, paraphrase, transfer from native language, overgeneralization, and overelaboration.